TRANSFORMATIONAL ROLE OF LEADERS IN THE CONTEMPORARY WORLD: AN EXAMINATION OF CHANAKYA’S THEORY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
For many years, there has been discussion about leadership among academicians and researchers, which has resulted in the development of various forms of leadership from time to time. These theories have their origins in the ancient knowledge system, which has been described by several researchers and has effectively demonstrated the traits that a leader must have while in office. However, no primary data study has been included in the studies to examine whether these attributes are still practiced by different individuals. In order to bridge the gap, the current study uses the Leadership Practices Inventory to examine whether varied professionals possess Chanakya’s leadership traits. The research exhibited the similarities between the variables of the LPI and Chanakya’s qualities on leadership, and all the variables significantly influenced Transformational Leadership, except ‘Challenge the process’ and ‘Enable others to act’. This is the first study of its kind, and the findings can help professionals in all fields comprehend and use the Chanakya approach to leadership in their everyday lives. The studies on the practical application of ancient wisdom on various subjects will enable us to revive Vedic techniques and practices.
Keywords: Chanakya; Arthashastra; Lead ership Practices Inventory; Transformational; Leadership; Ancient Wisdom